2015
DOI: 10.5222/iksst.2015.058
|View full text |Cite
|
Sign up to set email alerts
|

Atletic Performance, Genetics and Gene Doping

Abstract: Derleme ÖZET Genom bilimi ve gen regülasyonu teknolojilerindeki geliş

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
(20 reference statements)
0
2
0
3
Order By: Relevance
“…Recent studies have indicated that several genes are involved in determining the performance of the players, both physiologically and psychologically. 25 Genetic models could be developed and used to find the optimal genetic endowment of a player to help scientists establish which genetic polymorphisms are advantageous for proper performance in different sports types. Therefore, the creation of genomic databases will be very useful for sport scientists.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that several genes are involved in determining the performance of the players, both physiologically and psychologically. 25 Genetic models could be developed and used to find the optimal genetic endowment of a player to help scientists establish which genetic polymorphisms are advantageous for proper performance in different sports types. Therefore, the creation of genomic databases will be very useful for sport scientists.…”
Section: Discussionmentioning
confidence: 99%
“…Bu gibi teknolojiler geliştirildikçe biyolojik olarak uyumlu nanoaygıtların vücutta farklı işlevlerde kullanılabileceği tahmin edilmektedir. 64,66 Bilim kurgu filmlerinden aşina olduğumuz, insan-makine arası hibrid türler ise belki de günümüzde mevcut olan mekanik protezlerin daha da geliştirilmesi ile çok uzak olmayan bir gelecekte yaşamlarımızda yerini alacaktır. Ampute sporcularda kullanılan bu şekildeki mekanik protezler ile sporcular normalden daha iyi bir performans göstererek daha iyi koşabilmekte veya daha iyi zıplayabilmektedir.…”
Section: Dopi̇ngle Mücadeleni̇n Tari̇hi̇unclassified
“…Sports events and competition success play an important role locally and internationally in today's societies. Regardless of their capacities and motivation for sport, very high success has been expected from the athletes, which led to the development of training science (1). The athletes' psychological disposition is a factor researchers increasingly consider key to sports performance (2).…”
Section: Introductionmentioning
confidence: 99%